CORRELATION BETWEEN ANTITUBERCULOSIS MEDICATION ADHERENCE AND HEALTH-RELATED QUALITY OF LIFE AMONG TUBERCULOSIS PATIENTS IN KLATEN - Suizke, Elfrida Claudia Febriene; Sutanto, Eviana Budiartanti; Sebong, Perigrinus Hermin (Jurnal Pranata Biomedika, 2026)
Background: Tuberculosis remains a major public health challenge in Indonesia, particularly in high-burden areas such as Klaten. Beyond clinical recovery, improving Health-Related Quality of Life (HRQoL) is an essential goal in tuberculosis management. Medication adherence plays a critical role in achieving successful treatment outcomes, as it contributes to symptom resolution, prevention of complications, and overall improvement in patients’ well-being. However, previous studies examining the relationship between adherence and HRQoL have shown inconsistent results, and empirical data in high-case settings remain limited.This study aimed to analyze the relationship between adherence to antituberculosis medication and HRQoL among tuberculosis patients in Klaten.Methods: An analytic observational study with a cross-sectional design was conducted among 85 respondents from 16 Community Health Centres in Klaten Regency between August and December 2025. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8), while HRQoL was measured using the 36-Item Short Form Survey (SF-36). Data were analyzed using Spearman’s rank correlation test.Results: A significant and strong positive correlation was found between medication adherence and HRQoL (p 0.001; r = 0.625; 95% CI: 0.451–0.785). Higher adherence was associated with better quality of life.Conclusion: Strengthening adherence support is essential to improve the overall well-being of tuberculosis patients.